Enhanced Mechanical and Multifunctional Properties of GNPs/CNTs Hybridized PLA Nanocomposites by Implementing Dual‐Processing of Pickering Emulsion‐Melt Blending Methods - Bozhen Wu; Yidong Wu; Maolin Zhang; Hongxin Guo; Tong Liu; Guangyi Lin; Tairong Kuang (Macromolecular Materials and Engineering, 2025)
Abstract Polylactic acid (PLA) composites with multifunctional properties and minimal filler content are increasingly in demand across various industries. However, achieving a balance between high mechanical strength, electrical conductivity, thermal conductivity, and electromagnetic interference (EMI) shielding remains challenging. In this study, a dual‐processing strategy combining Pickering emulsion templating and melt blending is presented to hybridize 1D carbon nanotubes (CNTs) and 2D graphene nanoplatelets (GNPs) within a PLA matrix. This approach successfully forms a stable dual‐filler network, ensuring uniform dispersion of the fillers. The results show that this method significantly enhances the performance of the resulting PM‐PGxCy composites (P: Pickering emulsion; M: melt blending; x and y: mass fractions of GNPs and CNTs, respectively). Specifically, the PM‐PG1.43C1.43 composite exhibits remarkable improvements in mechanical strength (56.2 MPa), electrical conductivity (43.5 S m−1), EMI shielding effectiveness (20.1 dB), and thermal conductivity (0.34 W m·K−1), outperforming composites prepared using either method alone. These findings indicate that the dual‐processing strategy effectively combines 1D and 2D fillers, facilitating superior interfacial interactions and enhancing the multifunctional properties of PLA‐based composites. This study offers a new approach to achieving high‐performance PLA composites with low filler content, offering significant potential for applications in electronics, packaging, and EMI shielding technologies.